A multi-componential methodology for exploring emotions in learning:: using self-reports, behaviour registration, and physiological indicators as complementary data - Eteläpelto, Anneli; Kykyri, Virpi-Liisa; Penttonen, Markku; Hökkä, Päivi; Paloniemi, Susanna; Vähäsantanen, Katja; Eteläpelto, Tuomas; Lappalainen, Vesa (Frontline Learning Research, 2018)
Studies on emotions in learning are often based on interviews conducted after the learning. Therefore, these do not capture the multi-componential nature of emotions and how emotions are related to the process of learning. We see emotions as dimensional and multi-componential responses to a personally meaningful events and situation. In this methodologically frontline study we developed a multi-componential methodology, which provides complementary information about emotions during learning. In this study, by using a within subject design of one person, we focused on emotions during the professional identity learning. In a laboratory setting, the subject was shown personally meaningful video extracts from a learning situation she had participated earlier. The data were gathered by using (i) self-reports of emotions via the Emotion Circle (EC) online assessment, (ii) measures of autonomic nervous system (ANS) activity via Electro-Dermal Activity (EDA) and Heart Rate Variability (HRV), (iii) behavioural registration of facial expression and gaze, and (iv) the Stimulated Recall Interview (SRI). Self-reports of emotions via EC, as well as the emotion-driven SRI were found to be productive, not only in detailing and explaining emotions experienced during watching the videos, but also in bringing about reflective learning and novel insight. EDA and HRV provided complementary information from the subject’s ANS activity during the learning process. EDA seemed to be a valid indicator of active and agentic learning, while HRV was found to be a promising indicator of creative and reflective learning.